Makcik PC : the effectiveness of its brand name to capture target market in Malacca / Siti Zamirah Othman (Faculty of Business and Management, 2008)
This research paper is aim to produce the result of the effectiveness of Makcik PC's brand name in capturing its target market in Malacca. As for the extension, to find the potential of this brand name to become as a global brand name. I am seeking information on the perception of people towards Makcik PC's brand name. The study intends to provide a comprehensive understanding on the correlation between the dimension of brand equity and Makcik PC's brand name. It attempts to relate the people interest such as behavior, awareness and perception towards the name of Makcik PC. The result of the research can be taken into consideration for MIMOS Berhad in evaluating its approach in naming this computer. This study is based on simple random sampling where its target population is Melaka Tengah's residents. The sample frame involves the target market of Makcik PC which includes small entrepreneurs, housewives and students from higher education institutes located at Melaka Tengah. Besides collecting secondary data, primary data also had been collected using questionnaires that have been distributed to 120 respondents. The most important finding of this study is Makcik PC able to capture its target market located in Melaka where majority of the respondents agrees with that. Other than that, the finding showed that Makcik PC's brand name could not able to penetrate international market. For perception of people towards Makcik PC's brand name, the finding indicated that majority of people in Malacca disagree with the name of Makcik PC. The correlation table also showed that all dimension of brand equity have significant correlation with Makcik PC's brand name except perceived quality.